Aydar-Arnasoy Lake System, Tuzkon Lake Chavok Fish. Ecological Characteristics Of The Aral Chavok Fish (Rutilus Rutilus Aralensis Berg) - S.M. Namozov; M.E. Ummatova (Zien Journals, 2024)
Today, the growing need for food on a global scale requires the efficient use of the biological potential of inland water bodies, including the rational use of fish stocks, as well as the potential of fish farming and fishing facilities. Due to its geographical location, Uzbekistan is separated from the oceans and seas of the world, due to which its ichthyofauna is in a very poor condition, that is, the list of fish breeding and fishing facilities is very short. The fish facility can be expanded at the cost of migration, but there are certain limits in this regard
Keywords: Fishing facilities; fish breeding